PERSEPSI PEGAWAI TERHADAP PENGAWASAN MELEKAT OLEH PIMPINAN DI DINAS PENDIDIKAN KABUPATEN TANAH DATAR - Chandra Dwi Putra (Universitas Negeri Padang, 2015)
This article describes the perception of employees about built in control the district office of education at Tanah Datar. The samples are 46 employees who obtained using total sampling techniques. The research instrument used is questionnaire with Likert Scale models that have been tested its validity and reliability. The data were analyzed through average score. The result showed that: the leader”had enough (3,47) conducted built in controll in planning, had enough (3,49) conducted built in control in recording and reporting, and had enough (3,42) conducted built in controll in develpment of employees”. So the total results show that the leader at district office of education at Tanah Datar had enough (3,46) conducted built in controll. Keyword :controlling, development, leader